Porosity Scale Evaluation of Shielded Metal Arc Welding (SMAW) Specimen using Dye Penetrant Testing - M Amin, Sri Yulis (Journal of Advanced Mechanical Engineering Applications, 2024)
Non-destructive Testing (NDT) is a term that refers to a group of non-invasive inspection procedures that are used to assess material qualities, components, and complete process units. Welding is an important process in the metal manufacturing industry. Mild steel has been widely employed as a construction frame material because mild steel beams, like any structural steel beam, have extremely high strength. The objective of this study is to investigate the defects on Shielded Metal Arc Welding (SMAW) by using Dye Penetrant Testing (DPT) and to optimize the parameter of the SMAW welding for better output according to The American Society of Mechanical Engineers (ASME) standard. The study found that there are two types of defects obtained that is porosity and crack but the porosity had been chosen as a defect that have been analysis. The Taguchi Method was used as the optimization method for welding parameter. The design summary was the L9 orthogonal array with 2 factors that is current and thickness. The signal to noise ratios was set to smaller is better because the smallest output is desired which to minimize the defects of the welding. The relationship between porosity with current and thickness are if the highest current applied to the high thickness, the lower porosity defects will occur. If the highest current applied to the lower thickness, the more porosity defects will obtain. It can be concluded that the optimized parameter in order to get the least amount of porosity in the welded specimen is 100A current and 6mm of thickness